Training on Making Colour full Paving Block Made from Plastic Waste in SMPN 4 Situbondo SATAP - Ani Listriyana; Vina Dzurrotoon Nafisah; Muhammad Nur Zuhudil (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Paving blocks, also known as concrete bricks, are one of the materials commonly used by the public with many uses. Paving type A for roads, paving type B for parking lots, paving type C for pedestrians and paving type D for parks and other uses. Related to waste management efforts in Indonesia, efforts have been made to process one of them by processing plastic waste into paving blocks. From the research results, the maximum compressive strength value was obtained in a mixture of 30% Polypropylene plastic: 70% fine aggregate with a compressive strength value of 16.11 MPa, this value can be included in quality class C which can be used for pedestrians. There is quite a lot of this plastic waste in the coastal environment of Situbondo, Gelung Village. Therefore, one of our programs is to provide training to junior high school students and the academic community at SMPN 4 Panarukan SATAP in processing colorful plastic into paving blocks